SELF CONGRUITY - Tengku Ahmad Helmi; Sri Gustina Pane; Ismail Nasution; Tri Kartika Yudha (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
This study examines the framework of the basic research model for Self-Congruity formed based on the dimensions of Actual-Self Congruity, Ideal-Self Congruity, Social-Self Congruity, Ideal-Social Self Congruity, Avoidance Similarty and Consumption Status. The framework of the research model refers to self-theoy and social identity theory because this research model was studied to see how much influence self-congruity has on hedonistic users and utilitarian users.